Hubungan Terpaan Iklan Promosi di Media Sosial (Facebook dan Instagram) dan Tingkat Kompetensi Komunikasi Ambassador Gen Y dengan Minat Membeli Paket Data Produk Telkomsel - Ayunandita, Tiara; ., Sunarto (Interaksi Online, 2018)
Telkomsel uses advertising promotion strategy through social media such as Facebook and Instagram and through the communication competence that Gen Y has to raise buying interest of Telkomsel’s packet data product among young generations which is Telkomsel’s market target. The aim of this research is to explain the relation between promotion advertising on social media (Facebook and Instagram) and level of communication competence of Gen Y ambassador with the purchasing interest of Telkomsel’s packet data product. Sample selection in this research uses probability sampling technique and purposive sampling technique. Population in this research consists university students in Semarang with the age between 18 to 24 years old, owns social media such as Facebook and Instagram and have a direct communication with Gen Y ambassador as much as 100 respondents. Data analysisis done by nonparametical statistics with Kendall Tau correlation. The result in this research shows that the first hypothesis about promotion advertisment exposure on social media (Facebook and Instagram) has a positive relation towards purchase interest of Telkomsel’s packet data product with the coefficient of correlation value of 0,42 and with a weak tight level and then the significance value of 7 more above than z table, then significance . The result of the second hypothesis shows that the level of the communication competence owned by the Gen Y ambassador has a positive relation to the purchasing interest of Telkomsel’s packet data product with the coefficient of correlation value of 0,44 and with a weak tight level and the signicance value of 7,3 more above than z table, then significance. The result of the tird hipotesis show that promotion advertisment exposure on social media (Facebook and Instagram) and the level of the communication competence has a positive relation towards purchase interest of Telkomsel’s packet data product with multiple correlation value of 5,9 and the significance of 8,8 more than table z, then significant